EVALUATING GENETIC PURITY OF QUALITY PROTEIN MAIZE (QPM) INBREDS AND HYBRIDS BY BIOCHEMICAL AND SSR MARKERS - P. Sanghamitra; A. Tiwari; L. K. Bose; N. N. Jambhulkar (Journal of Animal and Plant Sciences, 2017)
Four maize hybrids and their parental lines were used to find genetic purity through testing with four isoenzymes such as alcohol dehydrogenase (ADH), esterase (EST), acid phosphatase (ACP) and malate dehydrogenase (MDH) and evaluated with thirty pairs of simple sequence repeat (SSR) markers. Out of the four isoenzymes, only malate dehydrogenase could able to detect polymorphism between parental lines of the two hybrids and confirmed the hybridity. The enzyme was also able to distinguish the hybrids from their female parent.  However, it was failed to detect the off types in the parental lines and in the hybrids. Out of 30 SSR markers employed for assessing genetic purity of hybrids, seven SSR markers were found polymorphic and confirmed the hybridity. Out of seven SSR markers, only one primer (dupssr34) distinguished the three-way cross hybrid Shaktiman-1 from its single cross female parent. Using this primer, 87.5% genetic purity was confirmed in the hybrid. These results clearly demonstrated that dupssr34 marker could be successfully used to evaluate genetic purity of three-ways cross QPM hybrid, Shaktiman-1, and may be used in seed production programme.
Keywords: Genetic purity; Isoenzyme; QPM; SSR marker